The Ferredoxin-Like Proteins HydN and YsaA Enhance Redox Dye-Linked Activity of the Formate Dehydrogenase H Component of the Formate Hydrogenlyase Complex - Pinske, Constanze (Frontiers in Microbiology, 2018)
Formate dehydrogenase H (FDH-H) and [NiFe]-hydrogenase 3 (Hyd-3) form the catalytic components of the hydrogen-producing formate hydrogenlyase (FHL) complex, which disproportionates formate to H2 and CO2 during mixed acid fermentation in enterobacteria. FHL comprises minimally seven proteins and little is understood about how this complex is assembled. Early studies identified a ferredoxin-like protein, HydN, as being involved in FDH-H assembly into the FHL complex. In order to understand how FDH-H and its small subunit HycB, which is also a ferredoxin-like protein, attach to the FHL complex, the possible roles of HydN and its paralogue, YsaA, in FHL complex stability and assembly were investigated. Deletion of the hycB gene reduced redox dye-mediated FDH-H activity to approximately 10%, abolished FHL-dependent H2-production, and reduced Hyd-3 activity. These data are consistent with HycB being an essential electron transfer component of the FHL complex. The FDH-H activity of the hydN and the ysaA deletion strains was reduced to 59 and 57% of the parental, while the double deletion reduced activity of FDH-H to 28% and the triple deletion with hycB to 1%. Remarkably, and in contrast to the hycB deletion, the absence of HydN and YsaA was without significant effect on FHL-dependent H2-production or total Hyd-3 activity; FDH-H protein levels were also unaltered. This is the first description of a phenotype for the E. coli ysaA deletion strain and identifies it as a novel factor required for optimal redox dye-linked FDH-H activity. A ysaA deletion strain could be complemented for FDH-H activity by hydN and ysaA, but the hydN deletion strain could not be complemented. Introduction of these plasmids did not affect H2 production. Bacterial two-hybrid interactions showed that YsaA, HydN, and HycB interact with each other and with the FDH-H protein. Further novel anaerobic cross-interactions of 10 ferredoxin-like proteins in E. coli were also discovered and described. Together, these data indicate that FDH-H activity measured with the redox dye benzyl viologen is the sum of the FDH-H protein interacting with three independent small subunits and suggest that FDH-H can associate with different redox-protein complexes in the anaerobic cell to supply electrons from formate oxidation.